2016
DOI: 10.1016/j.healun.2016.01.510
|View full text |Cite
|
Sign up to set email alerts
|

Control of Cardiomyocyte Proliferation Through p53/Mdm2-Regulated MicroRNAs

Abstract: Heart failure is a leading cause of morbidity and mortality in Canada. As the quality of life and prognosis for these patients is poor, therapies to prevent and treat heart failure are urgently required. Adult cardiomyocytes (CM) are terminally differentiated cells with minimal regenerative capacity, making cardiac tissue particularly vulnerable to injury. Thus, defining the roadblocks responsible for adult CM cell cycle arrest lies at the core of developing regenerative therapies for cardiac diseases. We have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…microRNAs (miRNAs/miRs) are a type of non-coding single-stranded RNA of ~22 nucleotides in length, which have important regulatory functions within cells (5). In recent years, miRNAs have received increasing attention in the field of heart development (6)(7)(8). We previously identified that miR-29c-3p in serum from patients with CHD, and that its expression was significantly increased in the serum of pregnant women carrying fetuses with CHD compared with in that of normal pregnant women (9).…”
Section: Introductionmentioning
confidence: 99%
“…microRNAs (miRNAs/miRs) are a type of non-coding single-stranded RNA of ~22 nucleotides in length, which have important regulatory functions within cells (5). In recent years, miRNAs have received increasing attention in the field of heart development (6)(7)(8). We previously identified that miR-29c-3p in serum from patients with CHD, and that its expression was significantly increased in the serum of pregnant women carrying fetuses with CHD compared with in that of normal pregnant women (9).…”
Section: Introductionmentioning
confidence: 99%